2022
DOI: 10.1007/s00285-022-01729-z
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model for the estrogen paradox in breast cancer treatment

Abstract: Estrogen is known to stimulate the growth of breast cancer, but is also effective in treating the disease. This is referred to as the "estrogen paradox". Furthermore, short-term treatment with estrogen can successfully eliminate breast cancer, whereas long-term treatment can cause cancer recurrence. Studies highlighted clinical correlations between estrogen and the protein p53 which plays a pivotal role in breast cancer suppression. We sought to investigate how the interplay between estrogen and p53 impacts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Breast cancer is one of the most common malignant tumors to women, especially, hormone receptor-positive breast cancer [50] accounts for 60%-70% of all breast cancer cases [51] and endocrine therapy is currently the main treatment for this type of breast cancer [52]. Though treatments for the cancer have been greatly improved, a considerable number of patients will eventually develop resistance to endocrine therapy [53], leading to a poor prognosis. Previous studies indicated that endocrine resistance is resulted from multiple mechanisms, for instance, loss or mutation in estrogen receptor (ER) and deregulation of cell cycle signaling molecules [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is one of the most common malignant tumors to women, especially, hormone receptor-positive breast cancer [50] accounts for 60%-70% of all breast cancer cases [51] and endocrine therapy is currently the main treatment for this type of breast cancer [52]. Though treatments for the cancer have been greatly improved, a considerable number of patients will eventually develop resistance to endocrine therapy [53], leading to a poor prognosis. Previous studies indicated that endocrine resistance is resulted from multiple mechanisms, for instance, loss or mutation in estrogen receptor (ER) and deregulation of cell cycle signaling molecules [54,55].…”
Section: Discussionmentioning
confidence: 99%